2023
DOI: 10.1021/acsagscitech.3c00025
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Premised Nanobiopesticides for the Management of Phytopathogens and Pests

Abstract: Rising awareness of the risks regarding chemical formulations and the surging need for eco-friendly inputs in sustainable agriculture have driven the use of bacterial biocontrol agents to the frontline of plant protection. Bacterial biocontrol agents (BBCAs) have been preferred as feasible alternatives to synthetic formulations due to their increased specificity and safety. Nanotechnology has facilitated the better addressing of product development and performance concerns related to BBCAs. Leveraging nanotech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 166 publications
(246 reference statements)
0
2
0
Order By: Relevance
“…A. Gorczyca et al (2021) and A. Padmakumar et al (2023) concluded that the undoubted prospects for the development and widespread use of nanotechnology lie in the fact that nanoparticles of biogenic metals have extremely high activity and sizes corresponding to the size of living cells, contribute to an increase in yields, gross yields of crops and product quality; increase the efficiency of nutrient use and their intended use, and have a positive effect on reducing the toxicological burden on the environment due to a significant reduction in the gross volume of fertilizer and pesticide application. In addition, according to T. El-Saadony et al (2021), nanoparticles in fertilizers are more reactive, able to penetrate the epidermis, providing gradual release and targeted distribution, and therefore reducing excess nutrients, increasing their use efficiency, are crucial in reducing abiotic stress and heavy metal toxicity.…”
Section: Discussionmentioning
confidence: 95%
“…A. Gorczyca et al (2021) and A. Padmakumar et al (2023) concluded that the undoubted prospects for the development and widespread use of nanotechnology lie in the fact that nanoparticles of biogenic metals have extremely high activity and sizes corresponding to the size of living cells, contribute to an increase in yields, gross yields of crops and product quality; increase the efficiency of nutrient use and their intended use, and have a positive effect on reducing the toxicological burden on the environment due to a significant reduction in the gross volume of fertilizer and pesticide application. In addition, according to T. El-Saadony et al (2021), nanoparticles in fertilizers are more reactive, able to penetrate the epidermis, providing gradual release and targeted distribution, and therefore reducing excess nutrients, increasing their use efficiency, are crucial in reducing abiotic stress and heavy metal toxicity.…”
Section: Discussionmentioning
confidence: 95%
“…Gorczyca et al (2021) and A. Padmakumar et al (2023) concluded that the undoubted prospects for the development and widespread use of nanotechnology lie in the fact that nanoparticles of biogenic metals have extremely high activity and sizes corresponding to the size of living cells, contribute to an increase in yields, gross yields of crops and product quality; increase the efficiency of nutrient use and their intended use, and have a positive effect on reducing the toxicological burden on the environment due to a significant reduction in the gross volume of fertilizer and pesticide application. In addition, according to T. El-Saadony et al (2021), nanoparticles in fertilizers are more reactive, able to penetrate the epidermis, providing gradual release and targeted distribution, and therefore reducing excess nutrients, increasing their use efficiency, are crucial in reducing abiotic stress and heavy metal toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…A very recent paper by Ristroph et al on novel scalable nanocarrier formulations for pesticides has quickly received a large number of views. Examples of other papers on nanomaterials relevant for pesticide formulations are as follows: sustainable nanomaterial approaches to essential oil delivery for disease prevention in soy; pesticide formulation processes using polymeric nanoparticles; metal–organic frameworks for controlled release insecticide formulations; utilizing plant virus nanoparticles as delivery vehicles in soil; and bacteria-based nanobiopesticides for plant disease management . Other examples of novel applications that have been published this year are smart gene delivery systems for plants using amine-functionalized carbon dots, nitrogen-doped carbon dots to address drought stress in maize, and nanoparticles doped with micronutrients and P to reduce nutrient leaching to groundwater .…”
mentioning
confidence: 99%